Effective Branding of Pepsodent's Social Responsibility Marketing Campaign for Younger Generation - Desyra Sukma Dewanthi (Bina Nusantara University, 2023)
Objectives: The objective of this study is to investigate the effectiveness of Pepsodent's social responsibility marketing campaign branding for the younger generation. The study is conducted in the context of Pepsodent's Social Responsibility Marketing Campaign which is #SikatGigiSekarang and aimed at the younger generation, aged 18-34 years old who have purchased Pepsodent products and are aware of the campaign. Methods: This research utilizes an online questionnaire that is distributed to 200 respondents. The full-scale data is analyzed through SmartPLS and bootstrapping analysis to test for reliability, validity, convergent and discriminant validity, and the study's hypothesis to identify the relationship between variables. Results: The findings of the research shows that all of the variables, such as Brand Familiarity, Attitude towards the Campaign, Campaign Fit, Credibility, Brand Attitude, and Involvement with the cause all affect each other. Brand Familiarity has a positive and significant relationship with Campaign Credibility and Brand Attitude, Campaign Credibility also has a positive and significant relationship with Attitude toward the Campaign, and Involvement with the Cause also has a positive and significant relationship with Attitude toward the Campaign. Campaign Credibility and Attitude towards Campaign play a full mediation in the relationship. Campaign Fit and Campaign Credibility are also positive and significantly related. Conclusion: Findings of this research are similar to the original study. All of the hypotheses have been accepted which proves that all the variables in the research model have been pretty effective and have positive relationships between the variables when measured for the social responsibility marketing campaign of Pepsodent. The younger generation nowadays not only prefers well-known brands but also how connected the campaign is with a social cause that they support, therefore marketers must get their products ready and tie the participation with the cause to their campaign for their social responsibility marketing campaign. As a result, supporters are more inclined to promote the brand and buy its goods.